Longitudinal characterization of peripheral prion pathogenesis in Syrian hamsters experimentally inoculated with hamster-adapted Transmissible Mink Encephalopathy - Lee, Erin, author; Mathiason, Candace, advisor; Kendall, Lon, committee member; Bamburg, James, committee member (Colorado State University. Libraries, 2017)
Transmissible Spongiform Encephalopathies (TSEs) are a group of infectious, neurodegenerative diseases affecting animals, including humans. Caused by misfolded proteins called prions, TSEs are characterized by a long, asymptomatic incubation period that eventually cause neuronal death and progressive neurodegeneration. Transmissible Mink Encephalopathy (TME) is a rare TSE of mink. Syrian hamsters are susceptible to infection with TME, serving as a natural system of infection. Hyper strain (HY) of hamster-adapted TME is of particular interest due it its rapid spread into the lymphoreticular system (LRS) and blood, enabling us to study peripheral accumulation and spread of prions. Real-time quaking-induced conversion (RT-QuIC) is a rapid and sensitive assay used to detect prions, and has been used to investigate prion pathogenesis. In this study, we hypothesize that RT-QuIC can be used to detect splenic prions longitudinally throughout HY-TME infection, including during the asymptomatic phase of disease. Sixty male Syrian hamsters were extranasally (EN)-inoculated with HY-TME. We collected their spleen, blood, brain, and other tissues at early-, mid-, and late-disease course. Our study shows evidence for the temporal accumulation of prions both within the spleen and brain throughout disease. We detected RT-QuIC seeding activity in spleen and brain tissue harvested from HY-TME-inoculated hamsters in late disease, between 155 and 169 (terminal) days PI. Titers in the spleen ranged from 10-2 to 10-7. Titers in the brain ranged from 10-3 to 10-5. Additionally, we detected RT-QuIC seeding activity in the spleen of a clinical hamster before it was detectible in the brain, supporting previous work showing that the spleen is a site of peripheral prion accumulation before neuroinvasion. Our work validates the Syrian hamster, EN-inoculated with HY strain of hamster-adapted TME, as a system to evaluate peripheral prion burden within the LRS.
Keywords: detection; spleen; transmission; prion; blood; TME